FINANCIAL MANAGEMENT ASSISTANCE AT THE SALAFIAH ISLAMIC BOARDING SCHOOL IN LUMAJANG - Roshiful Aqli Qosyim; Ahmad Zarkasyi; Zainuddin (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2025)
The article describes financial management assistance at the Salafiah Islamic Boarding School in Lumajang. The research uses a constructive method. This community service activity was carried out using the participatory rural approach (PRA) method through counseling, demonstrations, and mentoring. Based on the research results, financial management assistance at the Salafiah Islamic Boarding School in Lumajang has been carried out through the following activities: financial management at the Salafiah Islamic Boarding School in Lumajang is carried out through a systematic process, starting from assistance in the preparation, assistance in the development of the Islamic Boarding School Revenue Budget plan, assistance in the receipt and expenditure of Islamic boarding school funds. The supervision system at the Salafiah Islamic Boarding School in Lumajang is carried out through evaluation and accountability.